Synthesis, structural characterizations, and electrochemical and spectroelectrochemical properties of novel peripherally octa-substituted metallophthalocyanines - KOCA, ATIF; KAKI, ESRA HACER (ELSEVIER SCIENCE SA, 2015)
In this study, we report the synthesis and characterization of N-(3-(4-methoxybenzyl)-5-(4-chorophenyl)-4H-1,2,4-triazol-yl)-4-methylbenzenesulfonamide (3) and peripheral functionalized ligand, 1,2-Bis(2-N-(3-(4-methoxybenzyl)-5-(4-chorophenyl)-4H-1,2,4-triazol-yl)-4-methylbenzene sulphonamide)- 4,5-dicyanobenzene (4). The reaction of compound 4 with the corresponding metal salts (Zn(CH3COO)(2), CoCl2, PbO) in the presence of DMAE with a catalytic amount of 1,8-diazabicyclo[5.4.0] undec-7ene (DBU) gave novel Zn(II) (5), Pb(II) (6) and Co(II) (7) phthalocyanine derivatives. These new metallophthalocyanines (5e7) have been characterized by using UVeVis, IR, H-1 NMR, C-13 NMR and MS spectroscopic data. Electrochemical and spectroelectrochemical measurements show that while CoPc gives a metal-based reduction process in addition to the ring-based reduction process, all other complexes give common ring reduction reaction of MPcs having redox inactive metal center. Redox behaviors of ZnPc, PbPc and CoPc were determined in solution with voltammetric and in situ spectroelectrochemical measurements. While ZnPc and PbPc complexes gave three reduction and one oxidation reactions, three reduction and two oxidation processes were observed with CoPc. All redox reactions of the complexes were chemically and electrochemically reversible except the second oxidation of CoPc. Analyses of voltammetric and in situ spectroelectrochemical measurements indicated metal based electron transfer reaction character for the first reduction and the first oxidation processes of CoPc. All other redox reactions of the complexes were proposed as ligand based processes. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Metallophthalocyanine; Microwave; Electrochemistry; Spectroelectrochemistry; Electropolymerization; MICROWAVE-ASSISTED SYNTHESIS; METAL-ION SENSOR; ZINC PHTHALOCYANINES; AROMATASE INHIBITORS; COBALT; BEHAVIOR; VOLTAMMETRY; MANGANESE; CRYSTAL; CO(II)